2012
DOI: 10.1002/jbt.20422
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of aminoguanidine on doxorubicin‐induced nephropathy in rats

Abstract: Reactive oxygen species and cytokines have been implicated in the nephrotoxicity induced by doxorubicin. The goal of the present study was to determine protective effect of aminoguanidine on doxorubicin-induced nephrotoxicity in rats. Different groups of male Wistar rats received doxorubicin (67.75 mg/kg/i.p./2 days), aminoguanidine alone and aminoguanidine (200 and 400 mg/kg/i.p./30 days) prior to doxorubicin, respectively. Doxorubicin significantly increased serum creatinine (505%), blood urea nitrogen (333%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…In this sense, Balercia et al [43] found that asthenozospermic men show greater levels of NO • than normozoospermic men and that the concentration of this gasotransmitter were negatively correlated with the sperm motility. In this way, our findings indicate that aminoguanidine can be employed for protecting against the effects of oxidative stress in sperm cells, which is consistent with the findings in other cells and tissues (lung: [44]; bladder: [45]; kidney: [46]; testis: [29]). Similarly, Abbasi et al [30,31] and Alizadeh et al [32,33] found that the in vivo administration of aminoguanidine improves the sperm concentration, motility, viability, normal morphology, mitochondrial membrane potential, and DNA integrity in varicocelized rats where the upregulation of the iNOS isoform may lead to high levels of ROS in the semen.…”
Section: Discussionsupporting
confidence: 89%
“…In this sense, Balercia et al [43] found that asthenozospermic men show greater levels of NO • than normozoospermic men and that the concentration of this gasotransmitter were negatively correlated with the sperm motility. In this way, our findings indicate that aminoguanidine can be employed for protecting against the effects of oxidative stress in sperm cells, which is consistent with the findings in other cells and tissues (lung: [44]; bladder: [45]; kidney: [46]; testis: [29]). Similarly, Abbasi et al [30,31] and Alizadeh et al [32,33] found that the in vivo administration of aminoguanidine improves the sperm concentration, motility, viability, normal morphology, mitochondrial membrane potential, and DNA integrity in varicocelized rats where the upregulation of the iNOS isoform may lead to high levels of ROS in the semen.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, DOX treatment caused a significant increase in TBARS levels and a significant decrease in GSH and CAT levels, when compared with the control group. These findings are in agreement with previous reports [25,29]. TBARS, a stable metabolite of the free radical mediated lipid peroxidation cascade, is widely used as a marker of oxidative stress and lipid layer destruction [30].…”
Section: Discussionsupporting
confidence: 93%
“…The most popular hypothesis is oxidative stress as a result of free radical production . The semiquinone form of DXR is a metabolite with a short life‐span and it starts a series of reactions that produce reactive oxygen species (ROS) after reacting with molecular oxygen . Moreover, it was reported that free radical production, mitochondrial dysfunction, calcium overload, and peroxynitrite also lead to DXR‐induced cardiotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…[2] The semiquinone form of DXR is a metabolite with a short life-span and it starts a series of reactions that produce reactive oxygen species (ROS) after reacting with molecular oxygen. [6,7] Moreover, it was reported that free radical production, mitochondrial dysfunction, calcium overload, and peroxynitrite also lead to DXR-induced cardiotoxicity. [8,9] It has been reported that DXR also increases inflammatory effects in the myocardium and the vasculature by increasing the expression of nuclear factor kappa-B (NF-B), a key regulator of genes that are involved in the inflammatory responses and immune responses.…”
Section: Introductionmentioning
confidence: 99%